A rapid, simple assay for digoxin. Issue 6 (June 1974) - Greenwood, Helena; Howard, M.; Landon, J.
Abstract : An extremely rapid radioimmunoassay for digoxin is described which is precise over the range of concentrations required to determine whether, or not, a patient has digoxin toxicity. The assay is based on the use of 125 -iodine-labelled digoxin and of a gel equilibration technique for the separation of antibody-bound and free digoxin. The results obtained compare closely with those by a conventional radioimmunoassay and the technique is sufficiently simple to enable its performance by relatively inexperienced laboratory staff.